A Serious Videogame as an Additional Therapy Tool for Training Emotional Regulation and Impulsivity Control in Severe Gambling Disorder - Tárrega, Salomé; Castro-Carreras, Laia; Fernández-Aranda, Fernando; Granero, Roser; Giner-Bartolomé, Cristina; Aymamí, Neus; Gómez-Peña, Mónica; Santamaría, Juan J.; Forcano, Laura; Steward, Trevor; Menchón, José M.; Jiménez-Murcia, Susana (Frontiers in Psychology, 2015)
Background: Gambling disorder (GD) is characterized by a significant lack of self-control and is associated with impulsivity-related personality traits. It is also linked to deficits in emotional regulation and frequently co-occurs with anxiety and depression symptoms. There is also evidence that emotional dysregulation may play a mediatory role between GD and psychopathological symptomatology. Few studies have reported the outcomes of psychological interventions that specifically address these underlying processes. Objectives: To assess the utility of the Playmancer platform, a serious video game, as an additional therapy tool in a CBT intervention for GD, and to estimate pre-post changes in measures of impulsivity, anger expression and psychopathological symptomatology. Method: The sample comprised a single group of 16 male treatment-seeking individuals with severe GD diagnosis. Therapy intervention consisted of 16 group weekly CBT sessions and, concurrently, 10 additional weekly sessions of a serious video game. Pre-post treatment scores on South Oaks Gambling Screen (SOGS), Barratt Impulsiveness Scale (BIS-11), I7 Impulsiveness Questionnaire (I7), State-Trait Anger Expression Inventory 2 (STAXI-2), Symptom Checklist-Revised (SCL-90-R), State-Trait Anxiety Inventory (STAI-S-T), and Novelty Seeking from the Temperament and Character Inventory-Revised (TCI-R) were compared. Results: After the intervention, significant changes were observed in several measures of impulsivity, anger expression and other psychopathological symptoms. Dropout and relapse rates during treatment were similar to those described in the literature for CBT. Conclusion: Complementing CBT interventions for GD with a specific therapy approach like a serious video game might be helpful in addressing certain underlying factors which are usually difficult to change, including impulsivity and anger expression.